Pyranocoumarins from the roots of Acronychia pedunculata - Ali N, Md.; J, Latip; E, Ismail (Malaysian Journal of Science, 2005)
Phytochemical investigation on the roots of Acronychia pedunculata (mentua Keminiyan) has been conducted. Several chromatographic methods have been employed to the ethyl acetate extract of the roots which led to the isolation of two pyranocoumarins namely alloxanthoxyletin and xanthoxyletin. Their structures were determined by extensive physical studies particularly NMR. The petroleum ether, ethyl acetate and ethanol extracts and the pure compounds of Acronychia pedunculata were tested for their cell growth inhibitory property against MCF-7 cell lines. The results showed that only the ethyl acetate extract was found to be moderately toxic with IC₅₀ values of 93µg/ml.